Strategi Pendidikan Islam Anak Usia Dini (PIAUD) Dalam Mengembangkan Kecerdasan Spiritual - Alzena Savaira Salimah; Muhammad Ibnu Al-Kautsar; Msy. Aisya; Muhammad Ahsan Al-Kautsar (STAI Bumi Silampari, 2023)
Early childhood Islamic education (PIAUD) has an important role in developing spiritual intelligence in children. Spiritual intelligence is an important aspect that needs attention in Islamic education, because it helps children develop a strong relationship with God, understand religious values, and behave according to Islamic teachings. This article discusses Islamic education strategies in developing spiritual intelligence in early childhood. Effective early childhood Islamic education strategies include the introduction of Islamic values in daily activities, the use of active and creative learning methods such as Islamic games and stories, and collaboration with parents and the community. Parents also have an important role in developing children's spiritual intelligence through support and assistance in daily religious practices. In this study, we describe the implementation of an Islamic education strategy in a PIAUD program as a case study. Evaluation of the implementation results showed a significant increase in the development of children's spiritual intelligence. These results provide a better understanding of the relationship between Islamic education strategies and the development of spiritual intelligence in early childhood. This research makes an important contribution to practitioners of Islamic education in designing PIAUD programs that are effective in developing children's spiritual intelligence. The implication of this research is the importance of a holistic approach in early childhood Islamic education, which includes religious values, creative learning methods, and close collaboration with parents and society.